2021
DOI: 10.5194/essd-13-1561-2021
|View full text |Cite
|
Sign up to set email alerts
|

The MALINA oceanographic expedition: how do changes in ice cover, permafrost and UV radiation impact biodiversity and biogeochemical fluxes in the Arctic Ocean?

Abstract: Abstract. The MALINA oceanographic campaign was conducted during summer 2009 to investigate the carbon stocks and the processes controlling the carbon fluxes in the Mackenzie River estuary and the Beaufort Sea. During the campaign, an extensive suite of physical, chemical and biological variables were measured across seven shelf–basin transects (south–north) to capture the meridional gradient between the estuary and the open ocean. Key variables such as temperature, absolute salinity, radiance, irradiance, nut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 118 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Once in shallow waters, tPOC is resuspended from bottom sediments to the water column (Jong et al., 2020) and transported farther offshore (Forest et al., 2014). Resuspension cycles constantly bring tPOC back to surface waters where it can be oxidized (Galeron et al., 2018; Massicotte et al., 2021) and degraded by bacteria to be ultimately outgassed as CO 2 (Jong et al., 2020). However, representing tPOC in regional models is not trivial as it requires coupling with bottom sediments and fine grid resolution in order to resolve the physical (i.e., tides, waves) and biogeochemical processes that drive tPOC dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Once in shallow waters, tPOC is resuspended from bottom sediments to the water column (Jong et al., 2020) and transported farther offshore (Forest et al., 2014). Resuspension cycles constantly bring tPOC back to surface waters where it can be oxidized (Galeron et al., 2018; Massicotte et al., 2021) and degraded by bacteria to be ultimately outgassed as CO 2 (Jong et al., 2020). However, representing tPOC in regional models is not trivial as it requires coupling with bottom sediments and fine grid resolution in order to resolve the physical (i.e., tides, waves) and biogeochemical processes that drive tPOC dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The Arctic dataset that we used to evaluate the algorithms was gathered from the following five cruises: the France-Canada-USA joint Arctic campaign MALINA [27], ICESCAPE (Impacts of Climate on Ecosystems and Chemistry of the Arctic Pacific Environment) 2010 and 2011 [28], TARA Oceans Polar Circle expedition [29] and the GREEN EDGE project [30]. Sampling of MALINA and GREEN EDGE (ship operation) was conducted aboard the Canadian icebreaker CCGS Amundsen.…”
Section: In Situ Datamentioning
confidence: 99%
“…The datasets used in this study can be found at MALINA [27], ICESCAPEs [28], TARA [29], GREEN EDGE [30] and PPARR [38].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The Arctic dataset that we used to evaluate the algorithms was gathered from the following five cruises: the France-Canada-USA joint Arctic campaign MALINA [25], ICESCAPE (Impacts of Climate on Ecosystems and Chemistry of the Arctic Pacific Environment) 2010 and 2011 [26], Tara Oceans Polar Circle expedition [27], and the GREEN EDGE project [28]. Sampling of MALINA and GREEN EDGE (ship operation) was conducted aboard the Canadian icebreaker CCGS Amundsen.…”
Section: In Situ Datamentioning
confidence: 99%
“…The datasets used in this study can be found at MALINA [25], ICESCAPEs [26], TARA [27], GREEN EDGE [28], and PPARR [36].…”
Section: Data Availability Statementmentioning
confidence: 99%